Forecasting solar radiation in Bani-Waleed town using a photovoltaic cell - Falih azeez; Baqer Joudah (College of Education for Pure Sciences, 2005)
In this study the instantaneous values of the total solar radiation find dropping on the horizontal surface foe Bani-Waleed town were measured using solar cell (6,25 xlO"' m ) apparatus, at every hour of the day (luring two months (from 1-12-99 to 1-2-2000) by measuring the voltage and current for the solar cell and by comparison with apparatus in weather observance station in Tripoli, it was found thai correction factor for the cell equals to (9.68) , sunshine ratio for Lv.cember 1999 was 67% and for January 2000 was 80% .